(untitled) (Research, Society and Development, 2025)
The Revised Bloom’s Taxonomy (RBT) is a system for organizing learning objectives into hierarchically structured dimensions according to their level of complexity, enabling constructive alignment between educational objectives, teaching activities, and assessment strategies. This article aims to analyze Biology items from the ENEM through the lens of the RBT, highlighting its usefulness in understanding the cognitive demands of the exam. The selection of items considered the skill required for their resolution (as defined by the ENEM Reference Matrix) and the psychometric parameters of discrimination, difficulty, and guessing. Two items were compared, both related to skill 15 of the Reference Matrix, but with divergent psychometric data. The items presented distinct cognitive levels: item 115 required higher dimensions of cognitive processing and knowledge compared to item 124. These findings are consistent with the differences observed in the microdata released by INEP. Thus, the study provides new evidence that RBT can be effectively applied to analyze the cognitive complexity of large-scale assessment items, such as those in the ENEM, contributing to reflections on the quality and intentionality of educational evaluations.